Historical roots and influential publications in the area of innovation in the creative industries: A cited-references analysis using the Reference Publication Year Spectroscopy. Issue 12 (9th March 2022) - Gohoungodji, Paulin; Amara, Nabil
ABSTRACT: This study explores the historical roots of the relatively new topic of innovation in the creative industries. We are interested in the contributions of researchers that have proven to be important to the topic over the long term. To do so, we used the Reference Publication Year Spectroscopy method. This method is based on the analysis of the frequency with which references are cited in publications in a specific research area, in our case, innovation in the creative industries. The study is based on a corpus of articles rigorously selected through a systematic review method of empirical articles published between 1998 and 2019. The results reveal 4585 cited references (CR) with 9 clearly identifiable peaks, the first of which is caused by the work of Schumpeter (1934) and the last by the book of Miles & Green (2008). Each of the peaks marks a major contribution to the evolution of the understanding of innovation in these industries with one or more publications, the majority of which have an economic basis. In addition, the study reveals that the three most influential publications in this field are the economically oriented books by Florida (2002), Caves (2000), and Miles & Green (2008).